47 Developing a study intervention: a realist review and consensus workshops to develop the namaste care intervention for people with advanced dementia prior to a feasibility study using a cluster randomised controlled trial in nursing care homes. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Walshe, Catherine; Kinley, Julie; Goodman, Claire; Bunn, Frances; Lynch, Jennifer; Sharpe, Rachel; Preston, Nancy; Patel, Shakil; Froggatt, Katherine
Abstract : Background: Clear intervention specification is important, but often absent or incomplete in study reports. Namaste Care is a complex intervention for people with advanced dementia, but is not well specified, can be implemented differently, with limited evidence of effect, nor understanding of its optimal delivery. Aims: a) To develop a programme theory(ies) of how the Namaste care intervention achieves particular outcomes, and in what circumstances. b) To refine and develop an evidence based Namaste Care intervention specification and training package acceptable to nursing care home staff and families. Methods: A two phase approach incorporating both a realist evidence review and consensus methods. Consensus workshops first explored readability, understandability and utility of stimulus materials with Namaste Care naïve care home staff. Next emerging findings from the review were presented to stakeholders (care home staff, volunteers and family carers) with experience of Namaste Care, and nominal group techniques used to identify how intervention materials and resources required to support implementation could be refined. Drawing on nominal group technique analytical methods, analysis considered both the frequency of statement rankings alongside a thematic analysis of reasoning for preferences. Findings: Presentation to Namaste Care naive staff resulted in changes to language and clarification of terms such as 'personal care'. Two consensus workshops (n=15 care home staff participants, n=1 family carer participant, n=1 volunteer participant) further refined materials. An additional section of the intervention guide developed between workshop one and two focused on organisational preparation for Namaste Care implementation. Issues such as intervention timing, frequency, focus and staffing requirements were identified as requiring further specification. Conclusion: A careful, staged, process of intervention specification and refinement revealed important issues that required attention. Addressing these before trial commencement could increase the likelihood of intervention fidelity.